(untitled) (GAIMS Journal of Medical Sciences, 2026)
Leprosy, caused by Mycobacterium leprae, is a formidable spectral disease with heterogeneous clinical manifestations that often overlap with dermatologic, neurologic, and systemic disorders. This case series illustrates leprosy’s capacity to masquerade as systemic lupus erythematosus (SLE), acute inflammatory demyelinating polyradiculoneuropathy (AIDP), and cutaneous lymphoma, emphasizing the challenges in timely diagnosis. Three patients demonstrated characteristic features of these distinct conditions: a young female presenting with malar rash and alopecia mimicking SLE, an elderly male with progressive neuropathy initially linked to AIDP following hepatitis B infection, and a middle-aged female with chronic indurated plaques and constitutional symptoms suggestive of cutaneous lymphoma. Despite initial diagnostic ambiguity guided by clinical and laboratory findings, histopathological evaluation with Fite-Faraco staining confirmed leprosy across all cases, revealing lepromatous to borderline tuberculoid subtypes. These cases reinforce leprosy’s reputation as a “great imitator” and underscore the necessity of including it in differential diagnoses for atypical presentations, even in non endemic regions. Histopathology remains indispensable for definitive diagnosis, particularly when classic signs such as sensory loss are subtle or not clinically apparent, or when nerve thickening is overlooked due to human error—underscoring the importance of sharpening clinical touch and thorough examination. Enhanced clinical suspicion and collaborative multidisciplinary evaluation are crucial to prevent diagnostic delays and mitigate long-term complications in this protean disease.